Unlocking Economic Growth: How Market Size, Exchange Rates, And Corruption Shape Foreign Direct Investment - Suardi, Soni; Syaiful, Syaiful; Halilintar, Muhamad (Dinasti Publisher, 2024)
This paper investigates the intricate relationships between market size, exchange rates, inflation, the Corruption Perception Index (CPI), Information and Communication Technology (ICT), and Foreign Direct Investment (FDI) on economic growth. Utilizing a panel data approach, the study analyzes data from Indonesia, China, and Singapore over the period 2019-2023, revealing that larger market sizes significantly attract FDI due to enhanced consumer potential and investment opportunities. Additionally, stable exchange rates are found to be crucial in mitigating risks associated with currency fluctuations, thereby increasing the attractiveness of a country for foreign investors. The findings also indicate that high levels of perceived corruption negatively impact economic growth by undermining governance and investor confidence. While the direct influence of ICT on economic growth was less pronounced, its role in enhancing operational efficiency and market access is acknowledged. The paper concludes with policy recommendations aimed at fostering a conducive investment environment through market expansion, exchange rate stability, anti-corruption measures, and ICT development. These insights contribute to a deeper understanding of the dynamics influencing FDI and provide a framework for policymakers to enhance economic growth in developing countries.